Analyzing Capital Flow Drivers Using the 'At-Risk' Framework : South Africa's Case - Goel, Rohit (IMF Working Papers; Working Paper ;, 2021)
Cross-border capital flows are important for South Africa. They fund the nation's relatively large external financing needs and have important financial stability implications evidenced by the large capital outflows and asset price selloffs during the COVID-19 pandemic. This paper adds to the literature on the drivers of South Africa's capital flows by applying the 'at-risk' framework--which differentiates between the likelihood of "extreme" inflows (surges) and outflows (reversals) and of "typical" flows--to both nonresident and resident capital flows. Estimated results show that among nonresident flows, the portfolio debt component is most sensitive to changes in external risk sentiment particularly during reversals. This applies to flows to the sovereign sector. Nonresident equity flows, both portfolio and FDI, are most sensitive to domestic economic activity especially during surges. This applies to flows to the corporate and banking sectors. Results also suggest that resident flows, in particular the FDI component, tend to offset nonresident flows, thus acting as buffers against funding withdrawal during periods of global risk aversion.